Games and Bereavement How Video Games Represent Attachment, Loss and Grief - Harrer, Sabine (transcript Verlag, 2018)
How can videogames portray love and loss? (S1(BGames and Bereavement(S0 (Banswers this question by analysing five videogames and conducting a participatory design study with grievers. Sabine Harrer offers both theoretical and practical perspectives on videogames and grief and suggests a design model for videogames to include grievers into game development. Overall, she explores how videogames can be used as contemporary medium for personal storytelling.s
Description based on print version record.
KU Select 2018: HSS Frontlist Books
Keywords: Social Science / Sociology; Social sciences; Electronic books